Prevalence of gnathostoma spinigerum infection in wild and cultured swamp eels in Vietnam - Tran Phu Manh Sieu (2018)
Human infections with Gnathostoma spinigerum frequently occur in southern Vietnam. Previous investigations have implicated infected swamp eels (Monopterus albus) as an important source of infection to humans. Because aquaculture of M. alba is an important farming activity in Vietnam, a 2-yr study was carried out to assess the relative importance of farmed and wild eels as potential sources of gnathostome infections in humans. Eels sold for public consumption in markets in southern provinces were examined between November 2005 and August 2007. Although no infections were detected in 1,020 cultured eels and 1,021 wild-caught eels collected from November 2005 to September 2006, larval G. spinigerum (AL3) infections were first detected in September 2006 in 28 of 230 wild-caught eels (12.2%) obtained from markets in Long An province and the Hoc Mon district of Ho Chi Minh City. Subsequently, monthly surveillance of wild-caught eels from these markets was carried out through August 2007. Prevalence of AL3 varied monthly, ranging from 0.8 to 19.6%. Both prevalence and infection intensity were higher during the latter part of the rainy season (August October). These results demonstrate that potentially zoonotic G. spinigerum larvae are common in wild eels in southern Vietnam and present a risk to consumers of raw fish dishes, especially during the annual rainy season. This information could help target public health education efforts in the region. The basis for the seasonal variation on eel infections is not known, but may be related to climate effects (flooding, higher temperatures) on intermediate host species ecology. © 2009 American Society of Parasitologists.